Stability analysis of isolated square footings with LimitState: GEO2D® (2023)
In the design of foundations, analysts have various applications that allow them to determine parameters of ultimate load capacity and safety factors. This article presents a study that seeks to analyze the results obtained from the modeling of foundations with geotechnical software of finite elements that integrate additional aspects of modeling that can vary with some degree of sensitivity the results of the design parameters. State-of-the-art modelers such as the one used in this study allow to involve in the analysis of foundations, characteristics about the boundary conditions of the land, the foundation materials and/or the width of the column. Several models of surface foundations were developed in stratified soil with the high performance geotechnical software LimitState:Geo2D (restricted version) and the formulation of Meyerhof and Hanna was used to validate the results. In order to analyze the impact on the design parameters, variations were made in the width of the foundation floor block, the foundation material and the section of the column, in all cases finding interesting differences in the results of the safety factor that in terms of engineering practice would mean impacts on construction costs, safety and risk, structural redundancy, reliability and vulnerability. © 2006-2018 Asian Research Publishing Network (ARPN).